Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1155/2018/7961509
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Porous Bioabsorbable Interbody Mg-Zn Alloy Cage in a Goat Cervical Spine Model

Abstract: Purpose Bioabsorbable Mg-based implants were previously assessed due to their intrinsic advantages, but Mg-based cage related research is limited. The specific blood supply and stress of the intervertebral environment can affect the function of Mg-based implants. The objective of this study was to investigate the performance of a bioabsorbable Mg-Zn alloy cage in anterior cervical discectomy and fusion (ACDF) and evaluate the control of degradation of the Mg-Zn cage surface modified by microarc oxidation (MAO)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 38 publications
1
17
0
Order By: Relevance
“…According to our previous findings, the size of experimental cage was modified with the specification of 12 mm × 10 mm × 4-5 mm and a 7-degree wedge angle (Figure 1) (12,13). The cage was tested in a universal testing machine, the modulus of elasticity in compression was 609.43±52.16 MPa, the yield strength was 151.59±8.34 MPa and the compressive strength was 392.62±16.…”
Section: Implantsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to our previous findings, the size of experimental cage was modified with the specification of 12 mm × 10 mm × 4-5 mm and a 7-degree wedge angle (Figure 1) (12,13). The cage was tested in a universal testing machine, the modulus of elasticity in compression was 609.43±52.16 MPa, the yield strength was 151.59±8.34 MPa and the compressive strength was 392.62±16.…”
Section: Implantsmentioning
confidence: 99%
“…However, in the ACDF model of goat cervical vertebrae bearing force, although the development of Mg alloys composition and the addition of surface coating methods to improve the degradation of Mg-based cage, such as an AZ31 cage with poly-ε-caprolactone (PCL) coating, porous Mg-Zinc (Zn) alloy cage with a microarc oxidation (MAO)/silicon-(Si-) containing coating and AZ31 cage with Si-containing coating, the whole degradation rate was nonlinear in the 24-week observation period, the early degradation rate was relatively fast, which resulted in the formation of local Mg ion concentration in tissues. Thus, the bone healing is still poor after implantation of Mg-based cage, and fusion success has never been reported (11)(12)(13). The main barrier that limits the clinical application of Mgbased cages is adverse reactions secondary to their fast degradation which may be caused by intervertebral pressure and blood supply different from unforced bones (14).…”
Section: Introductionmentioning
confidence: 99%
“…The fusion rates in control group of our study were 41.7% (5/12) and 58.3% (7/12) at 12 and 24 weeks, respectively. In other studies, which used the same criteria for the evaluation of interbody fusion based on CT scoring in goat model, autologous iliac bone with titanium plate and screws fixation was performed as the control group and the fusion scores both in 12 and 24 weeks were higher than the present study [28,29]. Another goat study used PEEK cage filled with an autologous graft in the control group and 2/6 indicated arthrodesis with solid bone bridging the fusion area through radiographic analysis after 12 weeks [7].…”
Section: Discussionmentioning
confidence: 52%
“…Ren et al reported in their study a comparable fusion rate for an autologous tricortical iliac crest bone graft and multiaminoacid copolymer/nanohydroxyapatite/calcium sulphate 24 weeks after surgery [59]. In a study presented by Xu et al, a porous bioabsorbable interbody Mg-Zn alloy cage without any additives was applied, however, no acceptable results of intervertebral fusion were confirmed either on CT or biomechanical evaluation [60]. Abbah et al presented unsatisfactory results of lumbar intervertebral fusion in the case of a BMP-free polycaprolactone/TCP scaffold compared to a bone autograft.…”
Section: Discussionmentioning
confidence: 96%